TANTANGAN MENGAJAR PELAJARAN FIQIH MATERI KHITAN PADA JENJANG SEKOLAH DASAR - Najmah Zahiroh; Susi Susanti; Rizka Maulidia Iffani Amalia; Joan Hesti Gita Purwasih (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2018)
Abstract This research was conducted to find out the teachers’ difficulty in explaining Fiqih lesson with circumcision (khitan) material. This research took place in MI Thoriqotus Sa’adah in Ngabab Village of Malang Regency. This study employed quantitative research method with interview and observation being the techniques of collecting data. Data analysis was carried out through data display, reduction, and description using Miles Huberman’s model. Cognitive learning theory was used as the analysis instrument to analyze the process of learning Fiqih with khitan material. The result of research showed that the challenge of teaching was affected by some factors: students have begun to be Mumayyiz, students have begun to understand sensitive parts of body, learning hour condition, monotonous seating style, and students’ habit of watching film. Theses obstacles could be dealt with by using a joyful learning strategy. It is in line with cognitive learning theory perspective encouraging the teacher to understand the students’ condition and learning material. Abstrak Penelitian ini dilatarbelakangi kesulitan guru dalam menjelaskan pelajaran Fiqih materi khitan. Lokasi penelitian ini di MI Thoriqotus Sa’adah Desa Ngabab Kabupaten Malang. Penelitian menerapkan metode penelitian kualitatif menggunakan teknik pengumpulan data wawancara dan observasi. Analisis data dilakukan melalui penyajian, reduksi dan dideskripsikan menggunakan model Miles Huberman. Teori pembelajaran kognitif sebagai pisau analisis digunakan untuk membedah proses pembelajaran Fiqih materi Khitan. Hasil penelitian menunjukkan bahwa tantangan mengajar dipengaruhi faktor siswa sudah mulai Mumayyiz, siswa mulai mengerti bagian-bagian sensitif, kondisi jam pelajaran, gaya tempat duduk yang monoton dan kebiasaan siswa menonton film. Kendala tersebut dapat diatasi melalui strategi pembelajaran yang menyenangkan. Hal ini selaras dengan perspektif teori pembelajaran kognitif yang mendorong guru untuk memahami kondisi serta materi pelajaran siswa.